O-024 Quantitative assessment of device-clot integration strength for thrombectomy. (23rd July 2022) - Liu, Y; Arturo Larco, J; Madhani, S; Kallmes, D; Brinjikji, W; Savastano, L
Abstract : Introduction: Both aspiration catheters (when clot ingestion is not achieved) and stent retrievers apply tensional force during device withdrawal to dislodge and remove clots. As the tensional force exceeds the device-clot integration strength (DCIS), the clot will disintegrate from the device and embolize. In this study, we aim to propose a standardized quantification method for DCIS and evaluate the DCIS for different thrombectomy devices and clot types. Materials and Methods: An in vitro testing platform was designed and built to quantify the DCIS. The platform includes a straight polyvinyl chloride tube with an inner diameter of 3.2 mm to mimic the human middle cerebral artery. A human clot analog was injected to the tube, and then the tube at the occlusion site was clamped down to replicate a recalcitrant occlusion. To conduct thrombectomy, an aspiration catheter (Sofia Plus, Microvention) or a stent retriever (Embotrap II, Cerenovus) was pushed to the occlusion site with the device's proximal end attached to a force transducer (MDB-2.5, Transducer Techniques) and a computerized linear stage (PT1-Z8, Thorlab). After the clot was integrated with the catheter tip or the stent basket, the linear stage pulled the device at 1 mm/s and the pulling force was recorded until the clot became disintegrated from the device. The difference between the peak pulling force and the friction force between the device and the vessel wall was defined as the DCIS. Two types of clots analogs (elastic and stiff) were tested in this study and were made by mixing human red blood cells, platelet-poor plasma, and platelet-rich plasma, and 2.27 wt% calcium chloride at volume ratios of 4:8:8:2 and 2:9:9:2, respectively. Each test was repeated for 5 times. Student t test was used to compare DCIS between different groups. Statistical significance was considered when p < 0.5. Results: For the elastic clot analog, the DCIS was 0.184 N (SD 0.018) and 0.191 N (SD 0.020) for the aspiration catheter and stent retriever, respectively, and the difference was not significant (p = 0.581). For the stiff clot analog, the DCIS was 0.097 N (SD 0.025) for the aspiration catheter, significantly lower (p < 0.001) than that (0.358 N [SD 0.057]) of the stent retriever. The DCIS was significantly (p < 0.001) lower for the stiff clot than the elastic clot using the aspiration catheter, while the DCIS was significantly (p < 0.001) higher for the stiff clot than the elastic clot using the stent retriever. Conclusion: This in vitro testing platform can perform a standardized quantification of the DCIS and may facilitate preclinical evaluation of thrombectomy devices. The stent retriever may perform better than the aspiration catheter in dislodging stiff clots. Disclosures: Y. Liu: None. J. Arturo Larco: None. S. Madhani: None. D. Kallmes: None. W. Brinjikji: None. L. Savastano: None.